"In Vielfalt vereint" – Die wirtschaftliche Lage in den Beitrittsländern nach 20 Jahren in der EU - Grega Ferenc; Joachim Ragnitz (Wirtschaftsdienst, 2024)
– Twenty years have passed since the largest enlargement of the European Union in history. During the eastern enlargement, 10 new member states entered the union, seven of which belonged to the former Eastern bloc. The new members have since experienced astonishing growth rates, closing the large gap between them and the rest of the EU. The GDP growth rates were consistently higher than those of the original members. Now, the EU must once again look east: the integration of the West Balkan countries would be a crucial step in the future development of the EU, not only economically, but also politically, provided the formal provisions of an accession are satisfied. A strong united Europe benefits all.
Keywords: F02; F15; O52; 330; EU-Mitgliedschaft; Wirtschaftslage; Bruttoinlandsprodukt; EU-Haushalt; EU-Staaten; EU-Mitgliedschaft; Wirtschaftslage; Bruttoinlandsprodukt; EU-Haushalt; EU-Staaten